MHD stagnation point flow and heat transfer over a stretching sheet in a blood-based casson ferrofluid with newtonian heating - Muhammad Khairul Anuar, Mohamed; Siti Hanani, Mat Yasin; Mohd Zuki, Salleh; Alkasasbeh, Hamzeh Taha (Akademia Baru, 2021)
The present study investigated the magnetohydrodynamic (MHD) flow and heat transfer on a stagnation point past a stretching sheet in a blood-based Casson ferrofluid with Newtonian heating boundary conditions. The ferrite Fe3O4 and cobalt ferrite CoFe2O4 ferroparticles suspended into Casson fluid represent by human blood to form blood-based Casson ferrofluid are numerically examined. The mathematical model for Casson ferrofluid which is in non-linear partial differential equations are first transformed to a more convenient form by similarity transformation approach then solved numerically by using the Runge-Kutta-Fehlberg (RKF45) method. The characteristics and effects of the stretching parameter, the magnetic parameter, the Casson parameter and the ferroparticle volume fraction for Fe3O4 and CoFe2O4 on the variation of surface temperature and the reduced skin friction coefficient are analyzed and discussed. It is found that the blood-based Casson ferrofluid provided up to 46% higher in temperature surface compared to blood-based fluid with the presence of magnetic effects.